Communication patterns in decision-making consultations between patients with advanced cancer and medical oncologists: A qualitative observational study - Daisy J.M. Ermers; Yvonne Engels; Henk J. Schers; Kris C.P. Vissers; Evelien J.M. Kuip; Marieke Perry (PLoS ONE, 2026)
Background Shared decision-making remains underutilized in patients with advanced cancer, despite its proven importance and ongoing efforts to improve its implementation. The influence of communication patterns during consultations on the limited application of shared decision-making in daily clinical practice is not yet well understood. This study explores communication patterns in medical decision-making consultations between patients with advanced cancer and medical oncologists. Methods We conducted a qualitative observational study of single consultations between patients with advanced cancer and their medical oncologists in a Dutch tertiary referral center. We used reflexive thematic analysis to generate key themes and categories that characterize communication patterns during these decision-making consultations. Results From January to March 2019, our analysis of 16 audio-recorded consultations generated four themes. 1. The medical oncologist is balancing between hope and realism. 2. There is little room for bad news. 3. The medical oncologist’s medical perspective is leading in medical decision-making. 4. The patient and medical oncologist have a shared focus on anticancer treatment. Conclusions In consultations between patients with advanced cancer and their medical oncologist, a self-reinforcing cycle of balancing hope and realism alongside a focus on life-prolonging anticancer treatment appears to impede the practice of shared decision-making.